Aminocyclopyrachlor Absorption and Translocation in Three Aquatic Weeds. Issue 1 (March 2015) - Israel, Trevor D.; Everman, Wesley J.; Richardson, Robert J.
Abstract : Studies were conducted to evaluate 14 C-aminocyclopyrachlor absorption and translocation in alligatorweed, waterhyacinth, and waterlettuce. Alligatorweed plants were treated at the seven-node stage, waterhyacinth was treated at the five-leaf stage, and waterlettuce was treated at the eight-leaf stage. All plants were pretreated with nonlabeled aminocyclopyrachlor at 0.14 kg ai ha −1 with 1% (v/v) methylated seed oil (MSO). 14 C-aminocyclopyrachlor was then applied to a protected leaf, and plants were harvested at 1, 2, 4, 12, 24, and 96 h after treatment (HAT). Radioactivity was determined in the treated leaf, shoots above treated leaf, shoots below treated leaf, roots, and growing solution. Absorption was rapid in all species and reached a maximum of 73, 72, and 73% of applied radioactivity for alligatorweed, waterhyacinth, and waterlettuce, respectively. In alligatorweed at 96 HAT, 43% of absorbed carbon-14 ( 14 C) was translocated to shoots above the treated leaf and 17% was translocated to lower shoot tissue. In waterhyacinth at 96 HAT, 56% of absorbed 14 C remained in the treated leaf, whereas 14 and 13% were found in parts above and below the treated leaf, respectively. In waterlettuce at 96 HAT, 50 and 33% of absorbed radioactivity was located above the treated leaf and in the growing solution, respectively. The low recovery of aminocyclopyrachlor in alligatorweed roots and growing solution might explain regrowth potential after herbicide treatment. These results also indicate that the lack of waterlettuce control with aminocyclopyrachlor is not due to reduced absorption or translocation.